[68Ga]Ga-interleukin-2 for imaging activated T-lymphocytes: biochemical characterization and phase I study in normal subjects - Signore, Alberto; Galli, Filippo; Varani, Michela; Campagna, Giuseppe; Bentivoglio, Valeria; Accardo, Antonella; Morelli, Giancarlo; Lauri, Chiara (European journal of nuclear medicine and molecular imaging, 2025)
This study aimed to develop a ready-to-use kit for Ga-labelling of interleukin-2 (IL2) facilitating PET imaging of activated T-lymphocytes. Human recombinant IL2 (hrIL2) and Aldesleukin (desIL2), conjugated with two different chelators (NODAGA and THP) were compared. Conjugated-IL2 was stored, freeze-dried at -80 °C and radiolabelled at room temperature. In vitro quality controls (iTLC, HPLC, SDS-PAGE, spectrometry and binding assays on activated T-lymphocytes) and in vivo biodistribution studies in BALB/c mice, were performed. The shelf life of the lyophilized kits was assessed up to 6 months of storage, by iTLC, HPLC and SDS-PAGE. First-in-human study was conducted in 5 volunteers by performing [ Ga]Ga-THP-desIL2 PET/CT acquisitions at several time-points, to assess biodistribution and dosimetry. Mass spectrometry showed that only one molecule of THP or NODAGA is bound to N-terminus of both IL2 proteins. The most efficient conjugation was observed for THP-desIL2. [ Ga]Ga-THP-desIL2 showed higher labelling yield (LY) (59.13 ± 2.58%), radiochemical purity (RCP) (97.91 ± 0.45%) and binding affinity to its receptor on activated T-cells (Kd = 0.584 nM/L) and a more favorable biodistribution in pre-clinical studies, with rapid kidney metabolism and lower liver uptake than [ Ga]Ga-NODAGA-desIL2 and [ Ga]Ga-THP-hrIL2. Lyophilized kit of THP-desIL2 remained stable at -80 °C up to 6 months maintaining high RCP and LY. Phase I study showed a rapid plasma clearance, renal metabolism, safety and favorable dosimetry. We developed an efficient lyophilized kit of THP-desIL2 for Ga-labelling at room temperature in GMP conditions, obtaining excellent in vitro and in vivo results. [ Ga]Ga-THP-desIL2 PET/CT studies in humans showed favorable dosimetry and safety, thus highlighting its potential for a wide range of clinical applications, particularly in immune-mediated diseases and cancer.